Teaching English as a Second Language in Sri Lankan Primary Schools : Opportunity and Pedagogy - Little, Angela W.; Shojo, Mari; Sonnadara, Upal; Aturupane, Harsha (Taylor and Francis, 2019)
Policy guidelines in Sri Lanka prescribe how and for how long English should be taught as a second language in primary education but practices on the ground may deviate. Opportunities for teaching and learning and pedagogy are key aspects of the process of learning. Using a large-scale survey this paper addresses (i) how much time is allocated to the teaching of English and how much time is lost, (ii) how English teachers use their time in primary education classrooms and (iii) the factors associated with student-centred learning and on academic learning in general. Around a quarter of the class time is lost through timetabling, teacher absenteeism, lesson start and finish times and teacher off task activity. Teachers who spend more time teaching in class are more likely to be in rural or estate schools and in schools with more facilities, and to have attended the Primary English Language Programme in the past. Teachers who spend more time on student-centred activities are more likely to be teaching Grade 3 than Grade 5, using remedial methods and holding an official ‘appointment’ as an English teacher. Policy implications for Sri Lanka are considered and points of comparison with policies and practices elsewhere raised.